Antibacterial Effect of Freshwater Crab Powder against Pathogenic Bacteria - Nebrass F. Chachain (Journal of Global Pharma Technology, 2016)
The objective of this study was to examine the antibacterial effect of crab powder on Klebsiella pneumonia, Pseudomonas fluorescens and Escherichia coli. Four concentration (250,300,400 and 500) mg /ml was used ,all bacteria giving the inhibition zone in all concentrations .Powder of freshwater Crab were show the highest inhibition zone (18mm) in bacteria in P. fluorescens at concentration 500 mg/ml and lowest inhibition zone to same species of bacteria was (11mm) at 250 mg/ml concentration .Keywords: Pathogenic Bacteria; Freshwater Crab Powder; Antibacterial Effect.